The effect of thin cell layer system in Vanilla planifolia in vitro culture - Wan AB Razak, Zuraida Ab Rahman1 and Sreeramanan Subramaniam, Goh Foong Jing, Wan Nur’ Aqilah binti (Current Botany, 2016)
This study was conducted using shoots of Vanilla planifolia as the explant for shoot induction using 2 protocols of thin cell layers (TCL) system. Shoots segment of 2-5 mm were cultured on half strength Murashige and Skoog (MS) semi-solid medium with of various concentration of benzylaminopurine (BAP) at 0, 1.0, 2.0, 3.0 and 4.0 mg/L and thidiazuron (TDZ) at 0, 1.0, 2.0, 3.0 and 4.0 mg/L respectively. Histological analysis of shoot formed showed that there were no differences between cross section and longitudinal section based on the appearance of cell structure of the shoots. For longitudinal section TCL system, medium containing 1.0 mg/L BAP and 1.0 mg/L TDZ was the optimal medium for shoot induction of V. planifolia. For cross section TCL system, 4.0 mg/L BAP and 3.0 mg/L TDZ were the best concentration for shoots induction of Vanilla. Hence, longitudinal section thin cell layer culture system is more suitable protocol for the micropropagation of Vanilla planifolia plantlets.